Metabolic Switch and Cytotoxic Effect of Metformin on Burkitt Lymphoma - Bagaloni, Irene; Visani, Axel; Biagiotti, Sara; Ruzzo, Annamaria; Navari, Mohsen; Etebari, Maryam; Mundo, Lucia; Granai, Massimo; Lazzi, Stefano; Isidori, Alessandro; Loscocco, Federica; Li, Jiejin; et al. (Frontiers in Oncology, 2021)
Altered cellular energetic metabolism has recently emerged as important feature of neoplastic cells. Indeed, interfering with cancer cell metabolism might represent a suitable therapeutic strategy. In this study, we aimed to assess glucose metabolism activation in human lymphomas and evaluate how metformin can exert its action on lymphoma cells. We studied a large series of human lymphomas (N=252) and an in vitro model of Burkitt lymphoma (BL) cells. We combined molecular biology techniques, including global gene expression profiling (GEP) analysis, qPCR and western blotting, and biochemical assays, aimed to assess pentose phosphate pathway, TCA cycle, as well as aerobic glycolysis rates. We found that glucose metabolism is overall enhanced in most lymphoma subtypes, based on GEP, with general shift to aerobic glycolysis. By contrast, normal B-cells only showed an overall increase of glucose usage during germinal center transition. Interestingly, not only highly proliferating aggressive lymphomas, but also indolent ones, like marginal zone lymphomas, showed the phenomenon. Consistently, genes involved in glycolysis were confirmed to be overexpressed in BL cells by qPCR. Biochemical assays showed that while aerobic glycolysis is increased, TCA cycle is reduced. Finally, we showed that metformin can induce cell death in BL cells by stressing cellular metabolism through the induction of GLUT1, PKM2 and LDHA. In conclusion, we unveiled glucose metabolism abnormalities in human lymphomas and characterized the mechanism of action of metformin in Burkitt lymphoma model.